Retrospective evaluation of negative‐pressure pulmonary edema in dogs (2006‐2018): 35 cases. Issue 3 (30th November 2021) - Herrería‐Bustillo, Vicente J.; Adamantos, Sophie; Lamb, Christopher R.; García‐Arce, Marta; Thomas, Emily; Saiz‐Álvarez, María Rocío; Cook, Simon; Cortellini, Stefano
Abstract: Objective: To describe the clinical characteristics and outcomes in a population of dogs with negative‐pressure pulmonary edema (NPPE) and to identify the main causes of the disease. To evaluate any associations with morbidity and mortality. Design: Retrospective study. Setting: Three university teaching hospitals and 2 private referral centers in the United Kingdom. Animals: Thirty‐five client‐owned dogs presented with NPPE. Interventions: None Measurements and main results: Data collected included patient characteristics, clinical history, clinicopathological abnormalities, radiographic features, treatments, and outcomes. The median age was 4 months (range 2–90) and median weight was 7.1 kg (range 1.7‐37.2). There were many causes of NPPE including leash tugs, near hanging, accidental choking, anatomical obstruction to airflow, and purposeful airway obstruction by people. The most common cause of NPPE was accidental choking (40% of cases). Dogs with an anatomical obstruction were older than 24 months. Hypoxemia with an increased alveolar‐arterial gradient was common on presentation. The majority of thoracic radiographs (65.7%) showed an alveolar or interstitial pattern in the caudodorsal area as previously described in the literature. Oxygen therapy was administered to 33 (94.3%) dogs. Furosemide was administered to 18 (51.4%) dogs. The median length of hospitalization was 2 days (range 0–14). Twenty‐eight (80%) dogs survived to discharge. Seven dogs were mechanically ventilated and only 2 of them (28.6%) survived to discharge. The requirement for mechanical ventilation was the only parameter associated with mortality ( P < 0.001). Conclusions: Most cases of NPPE occur in juvenile dogs. Different incidents associated with upper airway obstruction can produce an episode of NPPE. Choking on food or toys and near hanging have not been previously described in the veterinary literature as inciting causes of NPPE. The overall prognosis is good.